Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-87270-3
|View full text |Cite
|
Sign up to set email alerts
|

The Coronavirus Health and Impact Survey (CRISIS) reveals reproducible correlates of pandemic-related mood states across the Atlantic

Abstract: The COVID-19 pandemic and its social and economic consequences have had adverse impacts on physical and mental health worldwide and exposed all segments of the population to protracted uncertainty and daily disruptions. The CoRonavIruS health and Impact Survey (CRISIS) was developed for use as an easy to implement and robust questionnaire covering key domains relevant to mental distress and resilience during the pandemic. Ongoing studies using CRISIS include international studies of COVID-related ill health co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(220 citation statements)
references
References 62 publications
7
190
0
1
Order By: Relevance
“…Keeping a routine similar to how things were before COVID-19 improves sleep, emotional state and dedication to school homework. These results agree with other authors who reported that mood state is more strongly related to life changes than specific COVID worries ( 36 ). Being an older parent and part-time working also favor dedication to school homework, and parents with positive attitudes such as playing with their children or helping them with school homework have a favorable impact on their emotional state.…”
Section: Discussionsupporting
confidence: 93%
“…Keeping a routine similar to how things were before COVID-19 improves sleep, emotional state and dedication to school homework. These results agree with other authors who reported that mood state is more strongly related to life changes than specific COVID worries ( 36 ). Being an older parent and part-time working also favor dedication to school homework, and parents with positive attitudes such as playing with their children or helping them with school homework have a favorable impact on their emotional state.…”
Section: Discussionsupporting
confidence: 93%
“…Subjects were recruited via email and social media. Those who agreed to participate provided a digital informed consent of privacy protection disclaimer and completed the CoRonavIruS Health Impact Survey (CRISIS) (Nikolaidis et al, 2021 ), Italian version. The CRISIS was developed by the National Institute of Mental Health, the New York Child Mind Institute, and the New York State Nathan S. Kline Institute for Psychiatric Research, to provide a comprehensive assessment of the impact of COVID‐19 pandemic on daily lives (Nikolaidis et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Those who agreed to participate provided a digital informed consent of privacy protection disclaimer and completed the CoRonavIruS Health Impact Survey (CRISIS) (Nikolaidis et al, 2021 ), Italian version. The CRISIS was developed by the National Institute of Mental Health, the New York Child Mind Institute, and the New York State Nathan S. Kline Institute for Psychiatric Research, to provide a comprehensive assessment of the impact of COVID‐19 pandemic on daily lives (Nikolaidis et al, 2021 ). Along with demographic and clinical descriptive variables, CRISIS investigates exposure to COVID‐19, concerns, worries, mood states, life changes and daily behaviours (e.g., daily hours of sleep, routine physical activity and media use) related to COVID‐19 (Nikolaidis et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of anxiety in different contexts indicated, for instance, that it was significantly predicted by a large number of psychological and environmental factors such as serious problems at work, domestic violence, unhappy relationships with family, and higher levels of nonorganizational religious activity and intrinsic religiosity [13], as well as by both financial distress and other psychiatric or mental disorders [14]. It was also found that mood fluctuations and anxieties during the COVID-19 pandemic were predicted concurrently by the pandemic threats, as well as by prior mental health status, and lifestyle changes [15]. Gomes et al [16] found similarly that mental health problems were significantly related to perceptions of threat, sense of control, and previous coping with distressful encounters.…”
Section: Introductionmentioning
confidence: 95%